Waterborne high-solid-content wear-resistant epoxy coating and preparation method thereof

By using modified resin and modified nanoparticles in aqueous epoxy coatings, a cross-linked structure and a spherical wrapping structure are formed, which solves the shortcomings of existing aqueous epoxy coatings in terms of high wear resistance and rapid curing, and achieves the A coating with high solid content, rapid drying, excellent wear resistance, waterproof, aging resistance and corrosion resistance.

CN119432199AInactive Publication Date: 2025-02-14SHANGHAI HAOLI PAINT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510026597.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing water-based epoxy coatings have shortcomings in high wear resistance and rapid curing, and have low solid content, long drying time, insufficient waterproofness, aging resistance and corrosion resistance, which limits its application in the field of high performance demand.

Method used

Using water-based epoxy resin, modified resin, modified nanoparticles, etc., the cross-linked structure and spherical encapsulation structure of modified particles are formed through the prepolymer of the modified resin to enhance the wear resistance, water resistance, aging resistance and resistance of the paint. Corrosion performance.

Benefits of technology

It achieves excellent wear resistance of water-based high-solution solid wear-resistant epoxy coatings, while maintaining excellent waterproof, aging resistance and corrosion resistance, meeting the needs of high-performance industrial coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of coatings, in particular to a water-based high-solid-content wear-resistant epoxy coating and a preparation method thereof. The water-based high-solid-content wear-resistant epoxy coating is prepared from the following raw materials in parts by mass: 50 to 70 parts of water-based epoxy resin, 20 to 35 parts of modified resin, 5 to 8 parts of pigment filler, 4 to 8 parts of dispersing agent, 8 to 15 parts of curing agent, 1 to 3 parts of flatting agent, 5 to 15 parts of plasticizer, 0.5 to 1.5 parts of defoaming agent, 15 to 30 parts of modified particles and 100 to 150 parts of deionized water. According to the waterborne high-solid-content wear-resistant epoxy coating and the preparation method thereof provided by the invention, the finally prepared epoxy coating not only has excellent wear resistance, but also can keep excellent water resistance, aging resistance and corrosion resistance at the same time, meets the performance requirements of various industries in the prior art on high-performance high-solid-content epoxy coatings, and has wide application prospects. The market prospect is very excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to a water-based high-solid wear-resistant epoxy coating and a preparation method thereof. Background Art

[0002] With the improvement of environmental awareness and the concern for health and safety, water-based coatings are favored by the market due to their low VOC (volatile organic compound) emissions. Epoxy resins are widely used in heavy-duty anti-corrosion, flooring and other fields due to their excellent adhesion, chemical resistance and mechanical properties. However, traditional solvent-based epoxy coatings contain a large amount of organic solvents, which will evaporate into the air during the construction process, not only polluting the environment, but also potentially causing harm to human health.

[0003] In recent years, waterborne epoxy coatings have developed rapidly, but existing waterborne epoxy coatings generally have problems such as low solid content, slow drying speed, and poor chemical resistance. Especially in terms of high wear resistance and fast curing, the products currently on the market often cannot meet the needs of high-performance industrial coatings. Therefore, it is of great practical significance to develop a waterborne epoxy coating with high solid content, fast drying, good wear resistance and chemical resistance.

[0004] Although there are many water-based epoxy coating products on the market, most products still have problems such as low solid content, long drying time, insufficient water resistance, aging resistance and corrosion resistance, which limit their application in certain high-performance demand fields. The present invention aims to solve these problems and provide a more environmentally friendly, efficient and high-performance water-based high-solid wear-resistant epoxy coating. The present application provides a water-based high-solid wear-resistant epoxy coating and a preparation method thereof. The epoxy coating finally obtained not only has excellent wear resistance, but also can maintain excellent water resistance, aging resistance and corrosion resistance at the same time, which meets the performance requirements of various existing industries for high-performance high-solid epoxy coatings, and has a very excellent market prospect. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a water-based, high-solid, wear-resistant epoxy coating. The raw materials are, by mass: 50 to 70 parts of water-based epoxy resin, 20 to 35 parts of modified resin, 5 to 8 parts of color filler, 4 to 8 parts of dispersant, 8 to 15 parts of curing agent, 1 to 3 parts of leveling agent, 5 to 15 parts of plasticizer, 0.5 to 1.5 parts of defoaming agent, 15 to 30 parts of modified particles, and 100 to 150 parts of deionized water.

[0006] As a preferred solution, the mass ratio of the waterborne epoxy resin, modified resin, plasticizer and modified particles is (55-65): (25-30): (8-12): (20-25).

[0007] As a preferred solution, the mass ratio of the waterborne epoxy resin, modified resin, plasticizer and modified particles is (58-62): (28-30): (10-12): (22-24).

[0008] As a preferred solution, the epoxy equivalent of the waterborne epoxy resin is 400-700 g / eq.

[0009] As a preferred solution, the epoxy equivalent of the waterborne epoxy resin is 500-600 g / eq.

[0010] As a preferred scheme, the preparation method of the modified resin comprises the following steps: S1: adding itaconic anhydride, hydroxyethyl methacrylate and N,N-dimethylacrylamide to an organic solvent, adding an initiator under nitrogen protection and heating to 75-80°C for reaction for 3-4 hours to obtain a prepolymer; S2: adding the prepolymer to a deionized water solution containing 2-acryloyloxyethyl phosphate and acrylamide, adding an initiator again under nitrogen protection, and keeping the temperature at 80-85°C for reaction for 5-6 hours; S3: filtering the product obtained in S2, and then washing it with acetone and 5wt% sodium hydroxide solution in sequence, and finally washing it with deionized water, and completing vacuum drying at 60-65°C to obtain the product.

[0011] As a preferred solution, the mass ratio of itaconic anhydride, hydroxyethyl methacrylate and N,N-dimethylacrylamide is (8-10):(3-4):(1.5-2.5).

[0012] As a preferred solution, the mass ratio of the prepolymer, 2-acryloyloxyethyl phosphate and acrylamide is (10-13): (5-8): (40-50).

[0013] As a preferred solution, the initiator is potassium persulfate or ammonium persulfate.

[0014] The modified resin added in the present application can effectively improve the wear resistance of the water-based high-solid wear-resistant epoxy coating while maintaining excellent waterproof, aging and corrosion resistance. The modified resin added in the present application can help improve the integrity of the cross-linked structure of the modified resin by adding a prepolymer formed by itaconic anhydride, hydroxyethyl methacrylate and N, N-dimethylacrylamide, and realize a ring-opening reaction under an appropriate environment, thereby enhancing the internal cross-linking density of the modified resin, and then when added to the coating system, it can serve as a cross-linking site in the system, enhance the entanglement degree of the coating molecular chain, and then strengthen the strength of the three-dimensional network of the molecular chain, increase the free resistance and free path length of water molecules and active groups in the coating system, and then ensure that the modified particles are uniformly dispersed while ensuring good waterproof and anti-corrosion repellent effects, even in a highly active (high heat and high humidity) environment, it can still limit the contact opportunities of internal active molecules, thereby greatly reducing the reaction degree and reaction probability of internal side reactions.

[0015] The added modified nanoparticles can effectively form a stable intermolecular connection with the modified resin added in the present application through the spherical encapsulation structure formed by them, and the polyhydroxy structure on the surface. The existence of this effect can ensure that when the coating system is formed, the modified resin can serve as a viscous carrier for the modified particles, and while playing a role in uniform dispersion, a site structure of stable particles is formed inside the coating system. The existence of this structure greatly limits the segregation and migration of the modified particles after the coating is cured, thereby avoiding the negative effect of the polyhydroxy surface of the modified particles on water resistance. The modified particles can serve as the support and connection sites inside the coating system through the stable intermolecular connection, and can effectively become stress dissipation points when external forces act, thereby greatly reducing the size of the micro-void diameter of the surface particles of the coating when it is used, and weakening the penetration of water molecules and corrosive active molecules.

[0016] As a preferred solution, the pigment filler is at least one of iron oxide, carbon black, phthalocyanine blue, permanent red and titanium dioxide.

[0017] As a preferred solution, the dispersant is at least one of sodium lignin sulfonate, sodium polyphosphate, polyethylene glycol, hexadecyltrimethylammonium chloride, and polyoxyethylene alkylphenol ether.

[0018] As a preferred solution, the dispersant is sodium lignin sulfonate.

[0019] As a preferred solution, the leveling agent is at least one of polysiloxane leveling agents.

[0020] As a preferred solution, the leveling agent is modified polysiloxane.

[0021] As a preferred solution, the plasticizer is at least one of dibutyl phthalate, dioctyl phthalate, dioctyl adipate, dioctyl sebacate, epoxy soybean oil, epoxy butyl stearate and tributyl citrate.

[0022] As a preferred solution, the plasticizer is tributyl citrate.

[0023] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.

[0024] As a preferred solution, the preparation method of the modified particles comprises the following steps: S1: adding zinc oxide and zinc nitrate hexahydrate to deionized water, adding succinic anhydride and 3-aminopropylmethyldiethoxysilane, heating to 70-75°C and keeping warm for 2-2.5 hours, and obtaining a pretreatment solution after the reaction is completed; S2: adding the pretreatment solution to DMF and mixing evenly to form a mixed solvent, then adding 1,4-phthalic acid, stirring at 50-60 rpm for 20-30 minutes until the mixture is evenly mixed. S3: Then add 1,4-diaminobenzene and stir at 50-60 rpm for 20-30 min until uniform, then heat the reaction container at 2.5-3 ℃ to 120-140 ℃ and keep the temperature for 8-10 h, after the reaction is completed, naturally cool to room temperature and filter the product, wash with DMF and deionized water for 2-3 times respectively, finally, dry the washed product in vacuum at 60-65 ℃ for 6-8 h, and it is obtained after completion.

[0025] As a preferred solution, the mass ratio of zinc oxide, zinc nitrate hexahydrate, succinic anhydride and 3-aminopropylmethyldiethoxysilane is (1-1.5): (3-3.5): (0.8-1): (0.1-0.2).

[0026] As a preferred solution, the mass ratio of zinc nitrate hexahydrate, 1,4-phthalic acid and 1,4-diaminobenzene is (3-3.5): (1.8-2): (0.8-1.2).

[0027] As a preferred solution, the average particle size of the zinc oxide is 5-10 nm.

[0028] As a preferred solution, the average particle size of the modified particles is 420-520 nm.

[0029] As a preferred solution, the mass ratio of the curing agent, dispersant and modified particles is (10-14): (5-7): (20-25).

[0030] As a preferred solution, the mass ratio of the curing agent, dispersant and modified particles is (12~13): (5.5~6.5): (22~24).

[0031] As a preferred solution, the curing agent is at least one of diethyltriamine, triethyltetramine, m-phenylenediamine, phthalic anhydride and adipic anhydride.

[0032] As a preferred solution, the curing agent is diethyltriamine.

[0033] The second aspect of the present application provides a method for preparing the above-mentioned water-based high-solid wear-resistant epoxy coating, which specifically includes the following steps: S1: Mix the dispersant and deionized water and stir them thoroughly, then add the modified particles and pigments and fillers, and maintain the stirring speed at 120~160rpm to form a uniform slurry; S2: Add the water-based epoxy resin, modified resin and curing agent, maintain the stirring speed at 40~60rpm for 30~40min, ensure that the mixing is uniform, and then add the leveling agent, plasticizer and defoaming agent in turn. After each raw material is added, continue stirring for 20~30min to ensure uniform mixing; S3: Pass the obtained material through a 200~400 mesh sieve, and after filtering, immediately seal and store the product to obtain.

[0034] The beneficial effects of this application are: 1. The present application provides a water-based high-solid wear-resistant epoxy coating, which not only has excellent wear resistance, but also can maintain excellent waterproof, aging and corrosion resistance, meeting the performance requirements of various industries for high-performance high-solid epoxy coatings, and has a very excellent market prospect.

[0035] 2. A water-based high-solid wear-resistant epoxy coating provided in the present application can help improve the integrity of the cross-linked structure of the modified resin by adding a prepolymer formed by itaconic anhydride, hydroxyethyl methacrylate and N,N-dimethylacrylamide, realize a ring-opening reaction under appropriate conditions, and enhance the internal cross-linking density of the modified resin. When added to the coating system, it can serve as a cross-linking site in the system, enhance the entanglement of the coating molecular chains, and thereby enhance the strength of the three-dimensional network of the molecular chains, increase the free resistance and free path length of water molecules and active groups in the coating system, and thereby ensure good waterproof and anti-corrosion repellent effects while ensuring uniform dispersion of the modified particles. Even in a highly active (high heat and high humidity) environment, the contact opportunities of internal active molecules can still be limited, thereby greatly reducing the reaction degree and reaction probability of internal side reactions.

[0036] 3. A water-based high-solid wear-resistant epoxy coating provided in the present application can effectively form a stable intermolecular connection with the modified resin added in the present application through the spherical encapsulation structure formed by the added modified nanoparticles, and the presence of this effect can ensure that when the coating system is formed, the modified resin can serve as a viscous carrier for the modified particles, and while playing a role of uniform dispersion, a site structure of stable particles is formed inside the coating system. The existence of this structure greatly limits the segregation and migration of the modified particles after the coating is cured, thereby avoiding the negative effect of the polyhydroxy surface of the modified particles on water resistance. And the modified particles can serve as the support and connection site inside the coating system through the stable intermolecular connection, and can effectively become a stress dissipation point when an external force acts, thereby greatly reducing the size of the surface particle micro-void diameter of the coating when it is used, and weakening the penetration of water molecules and corrosion active molecules. DETAILED DESCRIPTION

[0037] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0038] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0039] Example 1 Example 1 The first aspect provides a water-based high-solid wear-resistant epoxy coating. The raw materials, in parts by mass, are: 60.5 parts of water-based epoxy resin, 28.5 parts of modified resin, 6.2 parts of pigments and fillers, 5.8 parts of dispersant, 12.4 parts of curing agent, 1.8 parts of leveling agent, 10.8 parts of plasticizer, 1.2 parts of defoaming agent, 23.5 parts of modified particles, and 110 parts of deionized water.

[0040] The epoxy equivalent of the waterborne epoxy resin is 550 g / eq, and the S-48 model product was purchased from Guangdong Suntech New Materials Co., Ltd.

[0041] The preparation method of the modified resin comprises the following steps: S1: adding 9.2 parts of itaconic anhydride, 3.6 parts of hydroxyethyl methacrylate and 2.1 parts of N,N-dimethylacrylamide to 100 parts of acetone, adding 0.08 parts of potassium persulfate under nitrogen protection, heating to 75°C for reaction for 3.5 hours to obtain a prepolymer; S2: adding 12.6 parts of the prepolymer to 380 parts of a deionized water solution containing 6.8 parts of 2-acryloyloxyethyl phosphate and 45 parts of acrylamide, adding 0.21 parts of potassium persulfate again under nitrogen protection, and keeping the temperature at 85°C for reaction for 5.5 hours; S3: filtering the product obtained in S2, and then washing it with acetone and 5wt% sodium hydroxide solution in sequence, and finally washing it with deionized water, and completing vacuum drying at 60°C to obtain the product.

[0042] The pigment and filler is phthalocyanine blue BGS; the dispersant is sodium lignin sulfonate; the leveling agent is modified polysiloxane BYK-333; the plasticizer is tributyl citrate; the defoamer is silicone defoamer BYK-088; and the curing agent is diethyltriamine.

[0043] The preparation method of the modified particles comprises the following steps: S1: 1.3 parts of zinc oxide and 3.3 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of deionized water, 1 part of succinic anhydride and 0.12 parts of 3-aminopropylmethyldiethoxysilane are added, the temperature is raised to 70°C and kept for 2 hours, and a pretreatment solution is obtained after the reaction is completed; S2: the pretreatment solution is added to 80 parts of DMF and mixed evenly to form a mixed solvent, then 1.8 parts of 1,4-phthalic acid are added, stirred at 60 rpm for 30 minutes until uniform, and preheated to 60°C and kept for 1 hour; S3: then 1.1 parts of 1,4-diaminobenzene are added and stirred at 60 rpm for 30 minutes until uniform, then the reaction container is uniformly heated from 3°C to 125°C and kept for reaction for 9 hours, after the reaction is completed, the reaction is naturally cooled to room temperature and the product is filtered, and the product is washed three times with DMF and deionized water respectively, and finally, the washed product is vacuum dried at 60°C for 8 hours, and the product is obtained after completion.

[0044] The average particle size of zinc oxide is 8.5 nm; the average particle size of modified particles is 491 nm.

[0045] The second aspect of Example 1 provides a method for preparing the above-mentioned water-based high-solid wear-resistant epoxy coating, which specifically includes the following steps: S1: Mix the dispersant and deionized water and stir them thoroughly, then add the modified particles and pigments and fillers, and maintain the stirring speed of 150 rpm to form a uniform slurry; S2: Add the water-based epoxy resin, modified resin and curing agent, maintain the stirring speed of 50 rpm for 35 minutes, ensure that the mixing is uniform, and then add the leveling agent, plasticizer and defoaming agent in turn. After each raw material is added, continue stirring for 25 minutes to ensure uniform mixing; S3: Pass the obtained material through a 300-mesh sieve, and after filtration, seal and store the product immediately.

[0046] Example 2 The specific implementation method of this embodiment is basically the same as that of Example 1, except that: the raw materials of the water-based high-solid wear-resistant epoxy coating, in parts by mass, are: 65 parts of water-based epoxy resin, 25 parts of modified resin, 6.2 parts of pigments and fillers, 7 parts of dispersants, 10.2 parts of curing agents, 1.8 parts of leveling agents, 11.8 parts of plasticizers, 1.2 parts of defoaming agents, 20 parts of modified particles, and 110 parts of deionized water.

[0047] Example 3 The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the water-based high-solid wear-resistant epoxy coating, in parts by mass, are: 55 parts of water-based epoxy resin, 30 parts of modified resin, 6.2 parts of pigments and fillers, 5 parts of dispersants, 13.6 parts of curing agents, 1.8 parts of leveling agents, 8.5 parts of plasticizers, 1.2 parts of defoaming agents, 20.5 parts of modified particles, and 110 parts of deionized water.

[0048] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, except that the raw materials of the water-based high-solid wear-resistant epoxy coating, in parts by mass, are: 70.5 parts of water-based epoxy resin, 15.5 parts of modified resin, 6.2 parts of pigments and fillers, 5.2 parts of dispersants, 12.4 parts of curing agents, 1.8 parts of leveling agents, 10.8 parts of plasticizers, 1.2 parts of defoaming agents, 30.5 parts of modified particles, and 110 parts of deionized water.

[0049] Comparative Example 2 The specific implementation method of this comparative example is basically the same as that of Example 1, except that the raw materials of the water-based high-solid wear-resistant epoxy coating, in parts by mass, are: 58 parts of water-based epoxy resin, 35.8 parts of modified resin, 6.2 parts of pigments and fillers, 5.8 parts of dispersants, 12.4 parts of curing agents, 1.8 parts of leveling agents, 10.8 parts of plasticizers, 1.2 parts of defoaming agents, 12.5 parts of modified particles, and 110 parts of deionized water.

[0050] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps: S1: adding 5.5 parts of itaconic anhydride, 6 parts of hydroxyethyl methacrylate and 0.6 parts of N,N-dimethylacrylamide to 100 parts of acetone, adding 0.08 parts of potassium persulfate under nitrogen protection and heating to 75°C for reaction for 3.5 hours to obtain a prepolymer; S2: adding 12.6 parts of the prepolymer to 380 parts of a deionized water solution containing 6.8 parts of 2-acryloyloxyethyl phosphate and 45 parts of acrylamide, adding 0.21 parts of potassium persulfate again under nitrogen protection, and keeping the temperature at 85°C for reaction for 5.5 hours; S3: filtering the product obtained in S2, and then washing it with acetone and 5wt% sodium hydroxide solution in turn, and finally washing it with deionized water, and completing vacuum drying at 60°C to obtain the product.

[0051] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps: S1: adding 9.2 parts of itaconic anhydride, 3.6 parts of hydroxyethyl methacrylate and 2.1 parts of N,N-dimethylacrylamide to 100 parts of acetone, adding 0.08 parts of potassium persulfate under nitrogen protection and heating to 75°C for reaction for 3.5 hours to obtain a prepolymer; S2: adding 5.8 parts of the prepolymer to 420 parts of a deionized water solution containing 2.8 parts of 2-acryloyloxyethyl phosphate and 55 parts of acrylamide, adding 0.21 parts of potassium persulfate again under nitrogen protection, and keeping the temperature at 85°C for reaction for 5.5 hours; S3: filtering the product obtained in S2, and then washing it with acetone and 5wt% sodium hydroxide solution in turn, and finally washing it with deionized water, and completing vacuum drying at 60°C to obtain the product.

[0052] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps: S1: 0.5 parts of zinc oxide and 4.5 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of deionized water, 1 part of succinic anhydride and 0.12 parts of 3-aminopropylmethyldiethoxysilane are added, the temperature is raised to 70°C and kept for 2 hours, and a pretreatment solution is obtained after the reaction is completed; S2: the pretreatment solution is added to 80 parts of DMF and mixed evenly to form a mixed solvent, and then 2 .5 parts of 1,4-phthalic acid, stir at 60 rpm for 30 minutes until uniform, preheat to 60℃ and keep warm for 1 hour; S3: then add 2.5 parts of 1,4-diaminobenzene and stir at 60 rpm for 30 minutes until uniform, then heat the reaction container at a constant rate of 3℃ to 125℃ and keep warm for 9 hours, after the reaction is completed, naturally cool to room temperature and filter the product, wash it with DMF and deionized water for 3 times respectively, finally, dry the washed product in a vacuum at 60℃ for 8 hours, and it is obtained after completion.

[0053] The average particle size of the modified particles was 591 nm.

[0054] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps: S1: 1.3 parts of zinc oxide and 3.3 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of deionized water, 1 part of succinic anhydride and 0.12 parts of 3-aminopropylmethyldiethoxysilane are added, the temperature is raised to 70°C and kept for 2 hours, and a pretreatment solution is obtained after the reaction is completed; S2: the pretreatment solution is added to 80 parts of DMF and mixed evenly to form a mixed solvent, and then 3 .2 parts of 1,4-phthalic acid, stir at 60rpm for 30min until uniform, preheat to 60℃ and keep warm for 1h; S3: then add 0.3 parts of 1,4-diaminobenzene and stir at 60rpm for 30min until uniform, then heat the reaction container from 3℃ to 125℃ and keep warm for 9h, after the reaction is completed, naturally cool to room temperature and filter the product, wash it with DMF and deionized water for 3 times respectively, finally, dry the washed product in vacuum at 60℃ for 8h, and it is obtained after completion.

[0055] The average particle size of the modified particles is 394 nm.

[0056] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 30 nm; and the average particle size of the modified particles is 764 nm.

[0057] Performance Evaluation Abrasion resistance: The epoxy powder coatings prepared in the examples and comparative examples were tested for abrasion resistance according to the standard GB / T 1768-2006, 1kg / 1000r, CS-17 wheel, and the test values ​​were the average of 10 tests and recorded in Table 1.

[0058] Waterproofness test: The sessile drop method was used to test the water contact angle of the coating surface after curing of the epoxy coating obtained in the embodiment and the comparative example. The coating thickness was 0.05 cm, the water drop size was 2.5 μL, and the time was 30 s. The water contact angle of the coating surface was obtained. The test value was the average of 10 tests and recorded in Table 1.

[0059] Aging resistance test: After the epoxy coatings prepared in the embodiments and comparative examples were cured, samples with a coating thickness of 0.05 cm were obtained. The samples were placed in a constant temperature and humidity chamber at 68±3°C and a relative humidity of 75±3% for 3 months, and then observed for blistering, oxidation and cracking. If so, it was unqualified, otherwise it was qualified. The qualified rate results of 50 groups of samples in each group were recorded in Table 1.

[0060] Salt spray resistance test: After the epoxy coatings prepared in the embodiments and comparative examples were cured, samples with a coating thickness of 0.05 cm were prepared. 5 wt% NaCl was used as the test solution. The temperature conditions were 38°C and the relative humidity was 90%. The salt spray resistance test was carried out with an inclination angle of 20°, uniform spraying, a spray pressure of 1.5 bar, and a test time of 800 h. After completion, whether there was blistering, oxidation, and cracking was observed. If there was, it was unqualified, otherwise it was qualified. The qualified rate results of 50 groups of samples in each group were recorded in Table 1.

[0061] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of wear resistance, waterproof performance, aging resistance and corrosion resistance. This is mainly due to the combined effect of the modified resin and modified particles added as specified in the present application and other matching technical solutions. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A water-based high-solid wear-resistant epoxy coating, characterized in that: The raw materials are as follows: 50-70 parts of waterborne epoxy resin, 20-35 parts of modified resin, 5-8 parts of pigment and filler, 4-8 parts of dispersant, 8-15 parts of curing agent, 1-3 parts of leveling agent, 5-15 parts of plasticizer, 0.5-1.5 parts of defoaming agent, 15-30 parts of modified particles, and 100-150 parts of deionized water. The epoxy equivalent of the waterborne epoxy resin is 400-700 g / eq; Preparation method of the modified resin The following steps are involved: S1: adding itaconic anhydride, hydroxyethyl methacrylate and N,N-dimethylacrylamide to an organic solvent, adding an initiator under nitrogen protection and heating to 75-80°C for reaction for 3-4 hours to obtain a prepolymer; S2: adding the prepolymer to a deionized water solution containing 2-acryloyloxyethyl phosphate and acrylamide, adding an initiator again under nitrogen protection, and keeping the temperature at 80-85°C for reaction for 5-6 hours; S3: filtering the product obtained in S2, and then washing it with acetone and 5wt% sodium hydroxide solution in turn, and finally washing it with deionized water, and drying it under vacuum at 60-65°C to obtain the product; The mass ratio of itaconic anhydride, hydroxyethyl methacrylate and N,N-dimethylacrylamide is (8-10): (3-4): (1.5-2.5); The mass ratio of the prepolymer, 2-acryloyloxyethyl phosphate and acrylamide is (10-13): (5-8): (40-50); The initiator is potassium persulfate or ammonium persulfate; The pigment filler is at least one of iron oxide, carbon black, phthalocyanine blue, permanent red and titanium dioxide; The dispersant is at least one of sodium lignin sulfonate, sodium polyphosphate, polyethylene glycol, hexadecyltrimethylammonium chloride, and polyoxyethylene alkylphenol ether; The plasticizer is at least one of dibutyl phthalate, dioctyl phthalate, dioctyl adipate, dioctyl sebacate, epoxy soybean oil, epoxy butyl stearate and tributyl citrate; Preparation method of the modified particles The following steps are involved: S1: Mix zinc oxide and zinc nitrate hexahydrate and add them to deionized water, add succinic anhydride and 3-aminopropylmethyldiethoxysilane, raise the temperature to 70-75°C and keep it for 2-2.5 hours, and obtain a pretreatment solution after the reaction is completed; S2: Add the pretreatment solution to DMF and mix evenly to form a mixed solvent, then add 1,4-phthalic acid, stir at 50-60rpm for 20-30min until uniform, preheat to 50-60℃ and keep warm for 0.5-1h; S3: Then add 1,4-diaminobenzene and stir at 50-60rpm for 20-30min until uniform, then heat the reaction container at 2.5-3℃ to 120-140℃ and keep warm for 8-10h, after the reaction is completed, naturally cool to room temperature and filter the product, wash with DMF and deionized water for 2-3 times respectively, finally, dry the washed product under vacuum at 60-65℃ for 6-8h, and obtain the product after completion; The curing agent is at least one of diethyltriamine, triethyltetramine, m-phenylenediamine, phthalic anhydride and adipic anhydride; The defoamer is at least one of the silicone defoamers; The leveling agent is at least one of polysiloxane leveling agents.

2. The water-based high-solid wear-resistant epoxy coating according to claim 1, characterized in that: The mass ratio of the waterborne epoxy resin, modified resin, plasticizer and modified particles is (55-65): (25-30): (8-12): (20-25).

3. The water-based high-solid wear-resistant epoxy coating according to claim 2, characterized in that: The mass ratio of the zinc oxide, zinc nitrate hexahydrate, succinic anhydride and 3-aminopropylmethyldiethoxysilane is (1-1.5): (3-3.5): (0.8-1): (0.1-0.2).

4. The water-based high-solid wear-resistant epoxy coating according to claim 3, characterized in that: The mass ratio of zinc nitrate hexahydrate, 1,4-phthalic acid and 1,4-diaminobenzene is (3-3.5): (1.8-2): (0.8-1.2).

5. The water-based high-solid wear-resistant epoxy coating according to claim 4, characterized in that: The average particle size of the zinc oxide is 5-10 nm.

6. The water-based high-solid wear-resistant epoxy coating according to claim 5, characterized in that: The average particle size of the modified particles is 420-520 nm.

7. The water-based high-solid wear-resistant epoxy coating according to claim 6, characterized in that: The mass ratio of the curing agent, dispersant and modified particles is (10-14): (5-7): (20-25).

8. A method for preparing a water-based high-solid wear-resistant epoxy coating according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: Mix the dispersant and deionized water and stir them evenly, then add the modified particles and pigments and fillers, and keep stirring at 120~160rpm to form a uniform slurry; S2: Add water-based epoxy resin, modified resin and curing agent, keep stirring at 40~60rpm for 30~40min, ensure that the mixture is evenly mixed, then add the leveling agent, plasticizer and defoaming agent in sequence, and continue stirring for 20~30min after adding each raw material to ensure even mixing; S3: Pass the obtained material through a 200~400 mesh sieve, and seal the product immediately after filtering to obtain the obtained product.

Citation Information

Patent Citations

  • Corrosion-resistant light-reflecting paint

    CN105315816A

  • Outdoor uvioresistant wear-resistant epoxy floor coating and preparation method thereof

    CN112724789A

  • Water-based anticorrosive paint and preparation method thereof

    CN115109496A

  • Corrosion-resistant coating and preparation method thereof

    CN117264502A

  • Pressure-resistant shell high polymer material for LED lamp and preparation method of pressure-resistant shell high polymer material

    CN118562291A